2000
DOI: 10.1046/j.1365-246x.2000.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear globalP-wave tomography by iterated linearized inversion

Abstract: Summary Recent advances in global imaging have lead to tomographic mantle models with regional scale details. To improve these models further, we have extended the usual linearized approach to traveltime tomography to non‐linear tomography. Here ‘non‐linear’ means that seismic ray bending due to inferred velocity heterogeneity is taken into account in an iterative method in which inversion steps are alternated with 3‐D ray tracing to update ray paths and traveltimes. As a starting point for our non‐linear inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
229
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(257 citation statements)
references
References 34 publications
25
229
0
3
Order By: Relevance
“…Recent tomographic images from first arrivals and surface waves using data from a similar stations distribution as we use here show a high-velocity body in the upper mantle (Bezada 2013;Palomeras et al 2014) similar to the structures found in previous tomographic studies (Blanco & Spakman 1993;Calvert et al 2000;Bijwaard & Spakman 2000). This high-velocity body, possibly corresponding to oceanic lithosphere, has a slab-like structure dipping steeply towards the east.…”
Section: Geological Setting and Previous Analysissupporting
confidence: 81%
See 2 more Smart Citations
“…Recent tomographic images from first arrivals and surface waves using data from a similar stations distribution as we use here show a high-velocity body in the upper mantle (Bezada 2013;Palomeras et al 2014) similar to the structures found in previous tomographic studies (Blanco & Spakman 1993;Calvert et al 2000;Bijwaard & Spakman 2000). This high-velocity body, possibly corresponding to oceanic lithosphere, has a slab-like structure dipping steeply towards the east.…”
Section: Geological Setting and Previous Analysissupporting
confidence: 81%
“…The occurrence of intermediate depth seismicity suggests that there are deep heterogeneities in the upper mantle as confirmed by tomographic studies (e.g. Serrano et al 1998;Bijwaard & Spakman 2000;Bezada 2013). A big part of the shallow seismicity is located in southeastern Iberia and northeastern Morocco and it is related with the Trans-Alboran shear zone (Fig.…”
Section: Geological Setting and Previous Analysismentioning
confidence: 64%
See 1 more Smart Citation
“…Overall, the resolution is more even over the globe, but that is not to say that it is known precisely. With a few notable exceptions (e.g., Bijwaard & Spakman, 2000;Panning & Romanowicz, 2006), all classical P-and S-velocity models are obtained by a linear inversion using expression (11.2). The most important tool to assess the amplitude and shape of the models obtained by linearized inversions is the resolution operator, provided that the influence of the data errors is small (Equation 11.3).…”
Section: Isotropic Velocity Tomographymentioning
confidence: 99%
“…However, the global array of permanent seismometers that record seismic energy is confined almost exclusively to land-based sites. This limits the resolution of subsurface images, and results in relatively few local measurements from areas of great geological and tectonic interest (for example, the mid-ocean ridges and the Tibetan plateau) 1 To interrogate the Earth's subsurface at depths greater than a few kilometres, traditional seismology analyses seismic wave energy from earthquakes. Other energy recorded in seismograms, such as ambient Earth oscillation, is considered noise and is excluded from analysis.…”
mentioning
confidence: 99%